2013
DOI: 10.1172/jci65344
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-responsive miRNAs target argonaute 1 to promote angiogenesis

Abstract: In addition, data from tumor xenografts and human cancer specimens indicate that AGO1-mediated translational desuppression of VEGF may be associated with tumor angiogenesis and poor prognosis. These findings provide evidence for an angiogenic pathway involving HRMs that target AGO1 and suggest that this pathway may be a suitable target for anti-or proangiogenesis strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 49 publications
5
153
0
Order By: Relevance
“…Hypoxia down-regulates Dicer and thereby alters microRNA biogenesis. Furthermore, hypoxia-responsive miRNAs regulate argonaute1 (AGO1) and affect miR targeting (18). Our studies suggest that individual micro-RNA could be differentially regulated by transcriptional suppression.…”
Section: Discussionmentioning
confidence: 83%
“…Hypoxia down-regulates Dicer and thereby alters microRNA biogenesis. Furthermore, hypoxia-responsive miRNAs regulate argonaute1 (AGO1) and affect miR targeting (18). Our studies suggest that individual micro-RNA could be differentially regulated by transcriptional suppression.…”
Section: Discussionmentioning
confidence: 83%
“…Our previous study has also shown that let-7g could directly bind to THBS1 3 0 UTR and knock down its expression [10]. A recent study showed that several let-7 family members have hypoxia regulated/responsive elements in their promoters, and HIF-1a-induced let-7 could directly suppress AGO1 [11]. AGO1 is involved in miRNA-mediated silencing complex (miR-ISC) that causes gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…AGO1 is involved in miRNA-mediated silencing complex (miR-ISC) that causes gene silencing. VEGF-A is translationally suppressed by AGO1-miRISC under normoxia and let-7 can increase VEGF-A by repressing AGO1-miRISC leading to VEGF-A RNA release [11]. Accordingly, let-7g has multiple routes to increase VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of miRNA has been shown re cently in the regulation of cellular response to hypoxia. In particular, Let7 and miR103/107 favor the VEGF induction by targeting argonaute 1 protein [23] .…”
Section: Molecular Insights Into the Angiogenic Processmentioning
confidence: 99%